Comparison of psychological constructs in university athletes during a national competition - Villarreal Ángeles, Mario Alberto (2021)
Student-athletes have dual-role demands because in addition to being competitive level athletes, they haveacademic responsibilities to fulfill. This situation could generate psychological distress that may affect their quality of life.The purpose of the study was to compare psychological constructs in college athletes participating in the MexicanUniversity National Games. The sample comprised 402 athletes (Males = 210, Females = 192) who completed measuresof burnout, sports climate, self-esteem, depression, competitive anxiety, and body image. Athletes showed low self-esteem and burnout risk; females showed high self-esteem and males low anxiety. Team sports showed high depression,low anxiety and good sports climate scores. Southern athletes were prone to burnout and athletes from the center of thecountry showed high self-confidence. In conclusion, psychological constructs were different in males and females fromindividual and team sports and regions of Mexico during sports completion.